Synthesis and Cytotoxic Test of Halogen-Substituted Chalcone Against MCF-7 Breast Cancer Cells - Jamaran Kaban; Ginda Haro; Mimpin Ginting; Eti Meirina Brahmana (Universitas Gadjah Mada, 2022)
A series of chalcones was synthesized to be (E)-1-(4-chlorophenyl)-3-p-tolyprop-2-en-1-on (1), (E)-1-(4-chlorophenyl)-3-(4-tolyprophenyl) prop-2-en-1-on (2), (E)-1-(3-bromophenyl)-3-p-tolylprop-2-en-1-on (3), and (E)-1-(3-bromophenyl)-3-(4-isopropyl phenyl) prop-2-en-1-on (4) using irradiate microwave method with reaction time from 3, 6, and 8 min at 800 °C and 700 W. The compounds were characterized using TLC, UV-Vis, FTIR, 1H-NMR, and evaluated MCF-7 cancer cell cytotoxic test with Presto BlueTM. All compounds produced were in the form of yellow crystals. The results showed that compounds 2, 3, and 4 were potentially a Como prevention agent and inhibit cell proliferation with IC50 values of 37.24, 422.22, and 22.41 ppm, respectively. While compound 1 had IC50 1,484.75 and no cytotoxic effect. Further tests should be carried out for compounds 2, 3, and 4 against normal cells to measure the compound's safety for normal cells.